Identification of novel inhibitors of the ABC transporter BmrA - SARIYAR AKBULUT, BERNA; ALTINIŞIK KAYA, FATMA ECE; ÖZBEK SARICA, PEMRA (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2020)
The resistance of microbes to commonly used antibiotics has become a worldwide health problem. A major underlying mechanism of microbial antibiotic resistance is the export of drugs from bacterial cells. Drug efflux is mediated through the action of multidrug resistance efflux pumps located in the bacterial cell membranes. The critical role of bacterial efflux pumps in antibiotic resistance has directed research efforts to the identification of novel efflux pump inhibitors that can be used alongside antibiotics in clinical settings. Here, we aimed to find potential inhibitors of the archetypical ATP-binding cassette (ABC) efflux pump BmrA of Bacillus subtilis via virtual screening of the Mu.Ta.Lig. Chemotheca small molecule library. Molecular docking calculations targeting the nucleotide-binding domain of BmrA were performed using AutoDock Vina. Following a further drug-likeness filtering step based on Lipinski's Rule of Five, top 25 scorers were identified. These ligands were then clustered into separate groups based on their contact patterns with the BmrA nucleotide-binding domain. Six ligands with distinct contact patterns were used for further in vitro inhibition assays based on intracellular ethidium bromide accumulation. Using this methodology, we identified two novel inhibitors of BmrA from the Chemotheca small molecule library.
Keywords: BmrA; Efflux pump inhibitors; Antibiotic resistance; Nucleotide-binding domain; Molecular docking; Virtual screening; Chemotheca; MULTIDRUG EFFLUX PUMP; P-GLYCOPROTEIN; BACILLUS-SUBTILIS; NUCLEOTIDE-BINDING; DRUG-RESISTANCE; ATP-BINDING; IN-SILICO; STAPHYLOCOCCUS-AUREUS; REVERSAL AGENTS; ACRB